Modeling and characterization of shielded low loss CPWs on 65 nm node silicon - 王洪瑞 杨东旭 张莉 张雷 余志平 (Journal of semiconductors, 2011)
Coplanar waveguides（CPWs）are promising candidates for high quality passive devices in millimeterwave frequency bands.In this paper,CPW transmission lines with and without ground shields have been designed and fabricated on 65 nm CMOS technology.A physical-based model is proposed to describe the frequency-dependent per-unit-length L,C,R and G parameters.Starting with a basic CPW structure,the slow-wave effect and ground-shield influence have been analyzed and incorporated into the general model.The accuracy of the model is confirmed by experimental results.